Preventive Effect of Rebamipide Gargle on Chemoradiotherpy-Induced Oral Mucositis in Patients with Oral Cancer: a Pilot Study - Takashi Yasuda; Hiroshige Chiba; Takafumi Satomi; Akira Matsuo; Tadayoshi Kaneko; Daichi Chikazu; Hironobu Miyamatsu (Stilus Optimus, 2011)
Objectives: To assess the efficacy and safety of rebamipide in preventing chemoradiotherapy-induced oral mucositis in patients with oral cancer.Material and Methods: Patients with oral cancer treated with chemoradiotherapy (daily radiotherapy plus docetaxel hydrate once a week) were enrolled for this study. They were assigned in a double-blind fashion to receive either rebamipide gargle or placebo on the days of chemoradiotherapy. Oral mucositis was assessed using the WHO grading system. The primary endpoint of this study was the incidence of grade 3 - 4 mucositis after exposure to 40 Gy radiation (4 weeks). The secondary endpoint was the effect of rebamipide gargle on tumour response to chemoradiotherapy.Results: Twenty-four patients were randomly assigned to receive rebamipide gargle (n = 12) or placebo-gargle (n = 12) during chemoradiotherapy. The number of patients with severe mucositis (WHO ≥ 3) was higher in the placebo group than in the rebamipide group (83.3% vs. 33.3%, P = 0.036). In addition, no effect of rebamipide gargle on tumour response to chemoradiotherapy was recognized compared with the placebo group.Conclusions: For patients with oral cancer undergoing chemoradiotherapy, rebamipide gargle may contribute to decrease the severity of oral mucositis.